Orbital emphysema: A rare postoperative complication - dos Reis Fernandes, Breno [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Okamoto, Roberta [UNESP]; Neto, Oswaldo Belloti; Mandarino, Sydney; Silva, Jonathan; dos Santos Pereira, Rodrigo (Wolters Kluwer, 2018)
Orbital emphysema can be a rare and severe postoperative complication. Fast and critical diagnosis is essential to avoid permanent visual loss to the patient. Therefore, a case of a male patient victim of a motorcycle accident with a postoperative complication of orbital emphysema has been presented. The immediate diagnosis and treatment of the orbital emphysema revealed to be the main success factors for the resolution of this complication.
Keywords: Fracture; Head trauma; Orbital emphysema